Single-cell analyses identify independent aging processes that compete to determine cellular fate in budding yeast - Manuel Hotz; Rachel G. Kroll-Ling; Nathaniel H. Thayer; Daniel E. Gottschling (Proceedings of the National Academy of Sciences, 2026)
Phenotypic heterogeneity is prevalent during aging, yet its underlying molecular drivers remain poorly understood. In budding yeast, two distinct aging trajectories, characterized by either ribosomal DNA (rDNA) instability or mitochondrial decline, have been proposed to be mutually exclusive. Here, we systematically dissect the heterogeneity among aging yeast cells by combining single-cell transcriptomics with longitudinal fluorescence microscopy. Our data reveal distinct transcriptional responses that emerge in aging cells, highlighted by loss of rDNA silencing, a hypoxia response, and the environmental stress response (ESR). Contrary to expectation, we establish that ESR induction is not caused by rDNA instability but is instead a consequence of an early decline in mitochondrial membrane potential. However, the ESR is merely a biomarker of this decline and not itself a determinant of lifespan. While rDNA instability and mitochondrial dysfunction are anticorrelated as terminal phenotypes, we find that they are not necessarily mutually exclusive and can instead proceed concurrently within individual cells. Targeted genetic perturbations that are specific for one pathway do not impinge on the other, which is in contradiction to the idea of mutual inhibition between the two. We therefore propose a “competing hazards model”, where independent aging processes progress in parallel, and the observed mode of death is determined by which process first reaches a catastrophic failure point. Our work untangles the causal links between several aging pathways and provides a framework for understanding how distinct aging trajectories emerge from independent molecular events.